filmov
tv
Prove that `[ vec b xx vec c vec c xx vec a vec a xx vec b] = [ vec a vec b vec c]^2`
Показать описание
Doubtnut
Рекомендации по теме
0:02:33
Prove that `(vec(a) + vec(b)) xx (vec(a) - vec(b)) = 2 (vec(b) xx vec(a))`
0:03:17
Prove that : vec(a) . { vec(b) xx (vec(c) + vec(d))} = vec(a) . (vec(b)xx vec(c)) + vec(a) . ( ...
0:01:46
For any two vectors vec a and vec b , prove that (vec a xx vec b )^2= |vec a |^2 |vec b|^2 -(ve...
0:01:52
Prove that `(vec(a)-vec(b)) xx (vec(a) +vec(b))=2(vec(a) xx vec(b))`
0:02:53
Prove that (vec(A)+2vec(B)).(2vec(A)-3vec(B))=2A^(2)+AB cos theta-6B^(2). | 11 | VECTORS | PHYSI...
0:03:06
Prove that, vec(a) xx ( vec (b) + vec(c)) + vec(b) xx (vec(c) + vec(a)) + vec(c)xx(vec (a) + vec...
0:03:05
Prove that (vec(a)+vec(b)).(vec(a)+vec(b)) = |vec(a)|^(2) + |vec(b)|^(2) , if and only if vec(a...
0:03:21
Prove that `vec(a)xx(vec(b)+vec(c))+vec(b)xx(vec(c)+vec(a))+vec(c)xx(vec(a)+vec(b))=0`
0:01:21
If `vec(A) +vec(B) = vec(C)` and `A^(2) +B^(2) = C^(2)`, then prove that `vec(A)`
0:02:59
Prove that `vec(a).{(vec(b)+vec(c))×(vec(a)+2vec(b)+3vec(c))}=[vec(a)vec(b)vec(c)]`
0:03:21
Prove that ( vec a- vec b)dot{( vec b- vec c)xx( vec c- vec a)}=0 | 12 | SCALAR TRIPLE PRODUCT ...
0:02:52
Prove that `(vec(A)+2vec(B)).(2vec(A)-3vec(B))=2A^(2)+AB cos theta-6B^(2)`.
0:04:37
Let `vec(a)` and `vec(b)` be two nonzero vector. Prove that `vec(a) bot vec(b) hArr |vec(a)+vec(b)
0:02:30
For any vector vec a\\ a n d\\vec b\nprove that | vec a+ vec b|lt=| vec a|+| vec b|dot | 12 | S...
0:02:35
Prove that, (vec(a) - vec(b)) xx (vec(a) + vec(b)) = 2 ( vec(a) xx vec(b)) | 12 | PRODUCTS OF T...
0:02:01
For any to vectors ` vec A and vec B`, prove that |vec A xx vec B|^2 = A^2 B^2 - ( vec A. vec B)^2`
0:03:02
Prove that `(vec a +vecb).(vec a -vec b)`= `|a|^2+ |b|^2 lt= gt vec a_|_vecb`
0:01:46
For any two vectors `vec a` and `vec b` , prove that ` (vec a xx vec b )^2= |vec a |^2 |vec
0:01:30
prove that |A×B|²+(A.B)²=A²B²
0:06:04
Prove that `[ vec b xx vec c vec c xx vec a vec a xx vec b] = [ vec a vec b vec c]^2`
0:03:32
Prove that (vec(A) +2vec(B)) .(2vec(A) - 3vec(B)) = 2A^(2) +AB cos theta - 6B^(2). | 11 | VECTO...
0:01:44
for 2 vectors a and b prove the relation
0:02:23
If `|vec(a)+vec(b)||=|vec(a)-vec(b)|` then show that `vec(a)` and `vec(b)` are perpendicular to...
0:03:18
Two vectors ` vec A and vec B` are added. Prove that the magitude of the resultant v ector